Հայերենի որոշ հնչյունափոխությունների ժամանակաշրջանի ճշգրտման հնարավորությունը Վանի սեպագիր (ուրարտական) արձանագրությունների միջոցով - Սարգիս Այվազյան (ՀՀ ԳԱԱ հրատ.)
Урартский язык, который, на наш взгляд, является некой формой древнейшего армянского языка, старше древнеармянского (грабара) на 1000-1300 лет и имеет черты, характерные для фонетической системы армянского языка данного периода. Их сравнение с древнеармянским языком позволяет уточнить время некоторых фонетических изменений армянского языка. The Urartian, in our opinion, one of the forms of the ancient Armenian language, is 1000-1300 years older than early Old (Classical) Armenian and has facts peculiar to phonemic system of the Armenian language of this period. The phonetic comparison of these evidences with the Old Armenian allows specifing the period of some phonetic developments of the Armenian.
Keywords: Auxiliary Sciences of History; Philology; Linguistics; Language and Literature; Inscriptions; Epigraphy